Effects of pre-treatments and drying methods on the quality parameters of pumpkin powder - Lim, Jackson Hwa Keen (2017)
Pumpkin (Cucurbita sp.) is a popular fruit due to its high carotenoid content and medicinal value; but it is a highly perishable product that deteriorates over a short period of time due to microbial spoilage. Therefore, drying techniques are introduced to preserve the product. However, during drying, the product may undergo serious deterioration due to changes in temperature, thus affecting the physical or chemical properties of the product. The objective of this study is to determine the effects of pre-treatments and to evaluate the influence of drying methods on the physical and proximate properties of different parts of pumpkin powder. Each parts of pumpkin (skin, flesh, seed and unpeeled) were pre-treated by immersing in the blanching water (70˚C for 1 minute) and in the Ca(OH)2 solution ((1:7) for 25 minutes) prior to drying using oven (80 ̊C for 15 hours and 30 hours), rapid hot air (80 ̊C for 1 hour 15 minutes and 2 hours 45 minutes) and freeze (-110 ̊C for 96 hours) drying methods. The dried samples were grounded and sieved (250μm and 710μm). The pre-treatments showed a significant effect (p<0.05) on the physical and chemical properties of different parts of the pumpkin powder. The Ca(OH)2 pre-treated pumpkin powder resulted in the better physical properties with lowest moisture content (5.30-7.51%) and mean particle size (98.19-204.11 μm) and maximum density (219.46-781.63 kg/m3). On the other hand, different drying methods also showed significant influence (p<0.05) on the physical and chemical properties of different parts of pumpkin powder. Freeze drying method was found to be more effective in retaining proximate properties such as protein and fat and oven drying was more effective in produce powder with good physical properties such as lowest moisture properties, smallest particle size and highest densities value. Different part of pumpkin powder also shows the different physical and proximate properties with the skin part shows the good physical properties and seed part shows the highest proximate content compared to other parts of pumpkin powder. In conclusion, Ca(OH)2 pre-treatment and rapid hot air drying method is recommended for the production of the pumpkin powder with the better physical and proximate properties such as lower moisture content (5.45-7.55%), smaller particle size (112.05-256.46 μm), higher density (313.03-771.12 kg/m3), higher protein (7.96-30.16%) and fat (3.33-32.99%) content. It is recommended that the technique is applied to large scale production of high quality powder product in the future.